2023
DOI: 10.3389/fpubh.2023.1089565
|View full text |Cite|
|
Sign up to set email alerts
|

“You knew you had to be there, it had to be done”: Experiences of health professionals who faced the COVID-19 pandemic in one public hospital in Spain

Abstract: IntroductionThe COVID-19 pandemic highlighted the lack of a government contingency plan for an effective response to an unexpected health crisis. This study uses a phenomenological approach to explore the experience of healthcare professionals during the first three waves of the COVID-19 pandemic in a public health hospital in the Valencia region, Spain. It assesses the impact on their health, coping strategies, institutional support, organizational changes, quality of care, and lessons learned.MethodsWe carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…In contrast with other specialties, burnout did not result in mass resignation. An additional study of Spanish internists found that none took sick leave because of a strong collective spirit and a sense of solidarity with colleagues enhanced by institutional effectiveness in restructuring work shifts and a focus on teamwork--seen as a sign of support at the institutional level by the doctors [45].…”
Section: Internal Medicinementioning
confidence: 99%
“…In contrast with other specialties, burnout did not result in mass resignation. An additional study of Spanish internists found that none took sick leave because of a strong collective spirit and a sense of solidarity with colleagues enhanced by institutional effectiveness in restructuring work shifts and a focus on teamwork--seen as a sign of support at the institutional level by the doctors [45].…”
Section: Internal Medicinementioning
confidence: 99%
“…In contrast with other specialties, burnout did not result in mass resignation. An additional study of Spanish internists found that none took sick leave because of a strong collective spirit and a sense of solidarity with colleagues enhanced by institutional effectiveness in restructuring work shifts and a focus on teamwork, which was seen as a sign of support at the institutional level by the doctors [55].…”
Section: Internal Medicinementioning
confidence: 99%
“…Los resultados obtenidos en este estudio fueron similares al reportar una calidad de vida regular, pero la evaluación de las dimensiones puntúa primero el apoyo directivo, seguido por la motivación intrínseca y finalmente la carga de trabajo. Rodríguez y cols., 17 reportaron que profesionales de salud con un rol operativo percibieron mayor sensación de abandono por parte de su institución que sus colegas en roles gerenciales. Este hallazgo es similar al nuestro, en el cual existió significancia estadística entre el tipo de contratación y la percepción de calidad de vida.…”
Section: Tabla 3 Comparación De Características Demográficas Y Labora...unclassified